Gastric Glomus Tumour-A Rare Case Report - Nidhi Bansal; Arnav Roychoudhury (Journal of Krishna Institute of Medical Sciences University)
Gastric glomus tumour is a rare benign mesenchymal neoplasm composed of modified smooth muscle cells and neoplastic counter part of perivascular glomus body. Commonest site of glomus tumour being distal extremities (Subungual region of the finger tips, palm wrist and toes). Usually benign, may metastasize to liver and cause death; malignant behavior more likely if > 5 cm. In the gastrointestinal tract, stomach is the most common site of glomus tumors and present as submucosal masses that project into the lumen or out onto the serosa. Rare in solid organs – liver, kidney, Gastrointestinal (GI) tract; common GI site is stomach and are usually single tumor. It comprises of about 1% of all gastric mesenchymal tumours. After the 1st description of gastric glomus tumour in 1951 by Key et al only few cases have been reported. The correct assessment of the patient optimizes the chance for an accurate pre operative diagnosis and leads to a correct surgical or endoscopic intervention.